Combining Science and Metaphysics - Morganti, M. author. aut Link
XI, 211 p.
Keywords: Offering a new perspective on the debate concerning naturalism in philosophy, this book defends the autonomy of metaphysics while also making science centre stage. Three independent case studies provide a clear introduction to, and discussion of, key philosophical issues.